Superhydrophobic coatings for aluminium surfaces synthesized by chemical etching process. Issue 4 (1st October 2016) - Varshney, Priya; Mohapatra, Soumya Sanjeeb; Kumar, Aditya
ABSTRACT: In this paper, the superhydrophobic coatings on aluminium surfaces were prepared by two-step (chemical etching followed by coating) and one-step (chemical etching and coating in a single step) processes using potassium hydroxide and lauric acid. Besides, surface immersion time in solutions was varied in both processes. Wettability and surface morphologies of treated aluminium surfaces were characterized using contact angle measurement technique and scanning electron microscopy, respectively. Microstructures are formed on the treated aluminium surfaces which lead to increase in contact angle of the surface (>150°). Also on increasing immersion time, contact angle further increases due to increase in size and depth of microstructures. Additionally, these superhydrophobic coatings show excellent self-cleaning and corrosion-resistant behavior. Water jet impact, floatation on water surface, and low temperature condensation tests assert the excellent water-repellent nature of coatings. Further, coatings are to be found mechanically, thermally, and ultraviolet stable. Along with, these coatings are found to be excellent regeneration ability as verified experimentally. Although aforesaid both processes generate durable and regenerable superhydrophobic aluminium surfaces with excellent self-cleaning, corrosion-resistant, and water-repellent characteristics, but one-step process is proved more efficient and less time consuming than two-step process and promises to produce superhydrophobic coatings for industrial applications.